Research and Modeling of Lithium-Ion Batteries - Văn Ánh Dương; Phạm Thanh Tuân; Dương Tuấn Tùng; Đỗ Nguyễn Trung Kiên; Nguyễn Văn Dũng (Journal of Technical Education Science, 2025)
With the growing demand for Lithium-ion (Li-ion) batteries in personal electronic devices and energy storage systems, modeling their operational behavior has become essential for optimizing design and improving control strategies. Among various cathode materials, Lithium Nickel Manganese Cobalt Oxide (LiNiMnCoO₂ – NMC) is particularly noteworthy due to its high energy density, long cycle life, and adaptability under diverse operating conditions. This study develops a simulation model for the charge/discharge processes of Li-ion batteries employing NMC cathodes, using a system of partial differential equations (PDEs) to describe electrochemical kinetics, mass conservation, and charge conservation. The finite element method is implemented in MATLAB to solve the PDEs and analyze the spatial distribution of electric potential, current density, and ion concentration. Simulations are conducted at charge/discharge rates of 1C, 2C, and 10C. These C-rates represent typical real-world usage conditions: 1C corresponds to standard operation aimed at maximizing battery lifespan, 2C represents moderate load scenarios, and 10C simulates high-load conditions suitable for high-power applications such as electric vehicles. The simulation results provide a theoretical foundation for optimizing battery design and control, as well as a valuable reference for students and research scholars.